Design and simulation of stand-alone photovoltaic system supplying BTS in Iraq - Saja Mazin Sami; Anas Lateef Mahmood (Institute of Advanced Engineering and Science, 2021)
The problem of power outages is still present in most cities of Iraq as a result of the wars and crises experienced by Iraq and this makes it difficult to provide continuous electric power to the electrical devices. All telecommunications companies, including Zain, Asia cell, etc in Iraq used diesel generators as an alternative source to the national electricity grid, but this will adversely affect the environment and humans as a result of toxic emissions associated with the use of these generators. In this paper, a stand-alone PVsystem was designed and simulated to supply a base transceiver station (BTS) in Iraq. A BTS in Jadriyah, Baghdad with 4.177 kW load power belong to Zain Telecommunication Company was taken as a case study in this paper. The meteorological data of the Jadriyah region were taken from a weather station belong to the ministry of Sciences and Technology in Iraq for the year 2017. The simulation for this BTS was carried out using the Pvsyst simulation program. The financial analysis of the proposed system shows that it has small kWh unit price (0.108 /kWh).